God-image of Servant King as powerful but vulnerable and serving: Towards transforming African church leadership at an intersection of African kingship and biblical kingship to servant leadership - Magezi, Vhumani (HTS teologiese studies, 2015)
Christianity is mediated through culture and people’s cultural practices. One such cultural practice is African kingship. African kingship conveys on the ruler sovereignty, power, authority and supremacy over people under one’s jurisdiction. Intricately linked to respect for elders and those in power, African church leaders are at an intersection of the African kingship leadership style and the biblical kingship leadership style. Consciously or unconsciously, church leaders tend to embrace the African kingship approach to leadership and to a lesser extent biblical servant leadership. In such a situation, what God-image of biblical leadership could be discerned for constructive church leadership? In response, the God-image of Servant King as all powerful God, although vulnerable and serving, provides the framework for a transformative approach to church leadership in Africa.